Rheumatologists' understanding of refractory gout: a questionnaire survey in China. Issue 5 (May 2021) - Han, Xinxin; Yin, Yue; Cao, Yu; Chu, Xiaotian; Han, Yingdong; Di, Hong; Xu, Na; Zhang, Yun; Zeng, Xuejun
Objective: To explore the understanding of refractory gout in Chinese rheumatologists. Methods: We conducted an anonymous survey of rheumatologists attending an annual national academic conference on rheumatism. Results: Of the 910 rheumatologists who completed the questionnaire, 751 (82.5%) had received relevant continuing medical education (CME). Of these, 140 (18.6%) rheumatologists did not select xanthine oxidase inhibitors as the first treatment for patients with chronic tophaceous gout. Of all respondents, 113 (12.4%), 251 (27.6%) and 324 (35.6%) prescribed incorrect maximum doses of allopurinol, febuxostat and benzbromarone, respectively; this tendency was more pronounced in the non-CME group. Most rheumatologists agreed that complications and comorbidities increased the difficulty of gout management and considered the term refractory gout to describe those cases with uncontrolled symptoms, unmet treatment targets or non-shrinkage of tophi after standardized drug treatment. Moreover, 62.8% (472/751) of specialists considered that a diagnosis of refractory gout was appropriate for patients whose lifestyle and compliance failed to improve despite adequate education and regular urate-lowering therapy. Conclusions: Incorrect and inadequate drug therapy may contribute to some cases of refractory gout, especially in physicians without CME. An emphasis on non-drug therapy and the management of comorbidities and complications may reduce cases of refractory gout.